Isolated Vaginal Neurofibroma Presenting as Vaginal Wall Cyst: A Rare Case Report With Review of Literature - Sarita Nibhoria; Kanwardeep Kaur Tiwana; Manmeet Kaur; Richa Phutela (Tehran University of Medical Sciences, 2016)
Neurofibromas commonly involve peripheral nervous system. Isolated neurofibroma of vagina is very rare tumor and usually associated with Von Recklinghausen's disease. Vulva is the most frequent location of neurofibroma of genital tract followed by clitoris and labia. We present a rare case of neurofibroma of vaginal wall presented as vaginal cyst in a 52 year old female with no history of any other symptoms related to Recklinghausen's disease. Excision biopsy was done and on the histopathological examination non-encapsulated, well circumscribed mass composed of spindle shaped cells with wavy nuclei and bland nuclear chromatin was noted. Immunohistochemistry revealed strong positivity with S-100.